The UK experience: the National Patient Safety Agencyís Patient Safety Observatory (Italian Journal of Public Health, 2005)
The National Patient Safety Agency (NPSA) was set up in 2001 in order to make changes at a national level, and lead work on improving patient safety in England and Wales. A core function of the NPSA is to identify trends and patterns in patient safety problems, using its own National Reporting and Learning System (NRLS) and data from other sources.Almost all reports to the NRLS come directly from local risk management systems; staff can also report directly to the NPSA via an electronic form. By the end of August 2005, nearly 230,000 incidents had been reported to the NRLS; 76% of these were reported from acute/general hospitals.The analysis of data in the NRLS is a function of the NPSA’s Patient Safety Observatory (PSO), which has been established to quantify, characterise and prioritise patient safety issues in order to support the NHS in making healthcare safer. The PSO works with key national organisations which hold data relevant to patient safety, such as healthcare regulators, patient’s organisations, clinical negligence bodies and national information and statistics functions. Triangulating information from different data sources enables a fuller picture of the nature and severity of patient safety incidents to be obtained. The key challenges for the PSO are to strengthen the quality of NRLS data, extend the ways in which feedback from the NRLS is provided, and continue to develop methods and tools for the systematic analysis of the huge volumes of incidents reported to the NRLS.
Keywords: patient safety,; incident reporting; epidemiology; surveillance; data sources